2014
DOI: 10.1159/000357731
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Its Effects on Glucose Homeostasis, Cardiovascular Function and Immune Function

Abstract: In recent years there has been increasing interest in the non-skeletal effects of vitamin D. It has been suggested that vitamin D deficiency may influence the development of diabetes, cardiovascular dysfunction and autoimmune diseases. This review focuses on the current knowledge of the effects of vitamin D and its deficiency on cardiovascular function, glucose homeostasis and immune function, with a particular focus on children. Although, there is good evidence to show that there is an association between vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 154 publications
2
44
0
1
Order By: Relevance
“…It has been suggested that low vitamin D may reflect a risk factor in the development of insulin resistance and the pathogenesis of type 2 diabetes, as it affects either insulin sensitivity or beta‐cell function . We found an inverse association between 25(OH)D and f‐glucose when adjusted for age, and this agreed with other observational and intervention studies that demonstrated associations between vitamin D and f‐glucose . In our study population, 9.1% had IFG and the prevalence was significantly higher among children with vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It has been suggested that low vitamin D may reflect a risk factor in the development of insulin resistance and the pathogenesis of type 2 diabetes, as it affects either insulin sensitivity or beta‐cell function . We found an inverse association between 25(OH)D and f‐glucose when adjusted for age, and this agreed with other observational and intervention studies that demonstrated associations between vitamin D and f‐glucose . In our study population, 9.1% had IFG and the prevalence was significantly higher among children with vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 91%
“…This was in line with previous reports and may be explained by the difficulty in separating the effects of vitamin D and adiposity. However, there are discrepancies regarding this issue (10). Surprisingly, a difference was observed in gammaglutamyltransferase levels but not in aspartate aminotransferase or alanine aminotransferase levels, when comparing vitamin D-deficient children with their nondeficient counterparts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Vitamin D also affects many organs playing an important role in maintaining general health. Vitamin D deficiency may be associated with cardiovascular disease, diabetes, cancer, and autoimmune diseases (1). …”
Section: Dear Editormentioning
confidence: 99%